Lead (Pb) toxicity effect on physio-anatomy of bead-tree, jatropha, castor bean and Philippine-tung grown in water culture - Hamim Hamim; Hanifatunisa; Hadisunarso; Luluk Setyaningsih; Deden Saprudin (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hamim, Hanifatunisa, Hadisunarso, Setyaningsih L, Saprudin D. 2019. Lead (Pb) toxicity effect on physio-anatomy of bead-tree, jatropha, castor bean and Philippine-tung grown in water culture. Biodiversitas 20: 3690-3697. Heavy metal contamination in both land and water has been intensively studied because of their broad impact for the environment. Bead-tree (Melia azedarach), Jatropha (Jatropha curcas), castor bean (Ricinus communis) and Philippine tung (Reutealis trisperma) are kinds of non-edible oil-producing species, that are able to grow well on degraded lands and may have potential use for phytoremediation of heavy metals contaminated areas. This study aimed to analyze the response of bead-tree (Melia azedarach), jatropha (Jatropha curcas), castor bean (Ricinus communis) and Philippine-tung (Reutealis trisperma) to lead (Pb) contaminant in water culture experiment based on morphological, physiological and anatomical parameters. Two months old plants were transferred to the media containing Hoagland solution. After three weeks of planting, Pb (NO3)2 treatments with five concentrations, i.e. control (0 mM), 0.5 mM, 1 mM, 2 mM, and 3 mM were added together with Hoagland replacement and the plants were treated for three weeks. The growth, anatomical and physiological parameters were observed during the treatment until three weeks. The results showed that Pb treatment, especially with higher concentration, dramatically decreased plant growth, such as plant height, number of leaves, as well as shoot and root dry weight of all the species. Lead treatment triggered the emergence of free radicals and oxidative stress as indicated by a significant increase of malondialdehyde (MDA) content, while it decreased chlorophyll content of all the species. The higher concentration of Pb (NO3)2 caused the thickness of upper epidermis, lower epidermis, and spongy mesophyll tissue to decrease significantly which contributed to the decrease of leaves thickness. Among the species, Philippine-tung was the most tolerant of Pb toxicity. This species is potential to be used in phytoremediation program of lead-contaminated land such as gold mine area as well as heavy industrial areas.